Heads of Departments’ Perception of the Accreditation Roles of National Board for Technical Education in Quality Assurance in Nigerian Polytechnics - ONIYIDE , Olusegun Adepoju; SULYMAN , Kamaldeen Olohundare (International Journal of Educational Management, 2022)
This study was conducted to investigate the heads of departments’ perception of the accreditation roles of National Board for Technical Education (NBTE) in quality assurance in polytechnics in South West, Nigeria. The study adopted a descriptive research of survey design. The population for the study consisted of 307 Heads of Departments in five federal and 12 state Polytechnics in South West, Nigeria. The study covered eight out of the 17 Public polytechnics. Census technique was used to select 140 Heads of Departments from the polytechnics. The instruments used for data collection were two sets of questionnaire titled “Accreditation Roles of National Board for Technical Education Questionnaire (ARNBTEQ) and “Quality Assurance Questionnaire (QAQ)” with reliability coefficient of 0.61 and 0.88 respectively. The mean and standard deviation statistics were used to answer the four research questions raised while t-test statistics and Pearson product moment correlation coefficient (r) were employed to test the hypothesis formulated at 0.05 level of significance. The findings of the study revealed a moderate level of NBTE performance of accreditation roles and a positive relationship with quality assurance in public polytechnics in Nigeria. It was therefore recommended among others that, the National Board for Technical Education should improve on its accreditation roles to improve quality assurance in public polytechnics.